The Effectiveness of Combining Chest Physiotherapy and Steam Inhalation With Aromatherapy on Sputum Expectoration and Oxygenation Status In Pneumonia-Infected Toddlers - Novi Enis Rosuliana; Tetik Nurhayati; Kusmiyati Kusmiyati (Poltekkes Kemenkes Semarang, 2023)
Background: The leading causes of infant mortality worldwide are asphyxia, pneumonia, diarrhea, and malaria. In Indonesia, in the year 2020, there were 28,158 infant deaths, primarily attributed to congenital heart defects, accidents, diarrhea, and pneumonia. Pneumonia is an acute lower respiratory tract infection (involving the alveoli) caused by pathogens such as bacteria, viruses, or fungi, leading to respiratory distress and limited oxygen intake. Risk factors for pneumonia include inadequate exclusive breastfeeding, a history of prematurity, low birth weight, crowded living conditions, air pollution, incomplete basic immunization, malnutrition, and poverty. In 2017, there were approximately 120 million pneumonia cases worldwide, resulting in 1.3 million deaths. Pneumonia claims the lives of 100 children every hour. Methods: This study is a quantitative study using a quasi-experimental pre-test post-test with a control group design. The research population includes all toddlers undergoing examinations at the Cibeureum City Health Center in Tasikmalaya, with a sample size of 30 respondents divided into intervention and control groups. The sampling technique used in this study is consecutive sampling based on inclusion criteria. Data analysis was performed using the Wilcoxon Sign Ranks Test for dependent groups and the Mann Whitney test for independent groups. The instruments used were observation sheets related to sputum production and oxygenation status (respiratory rate and oxygen saturation). Results: The result of this research showed that the significance value for sputum production is 0.007, which is less than the p-value of 0.05. Regarding oxygenation status, including respiratory rate and oxygen saturation, the intervention provided to the intervention group yielded p-values of less than 0.005, specifically 0.001 for respiratory rate and 0.003 for oxygen saturation. Conclusion: This study demonstrates that the combination of chest physiotherapy and steam inhalation with aromatherapy is effective in improving sputum production, reducing respiratory rate, and increasing oxygen saturation in toddlers with pneumonia. Therefore, it is crucial in nursing care to implement the combination of chest physiotherapy and steam inhalation with aromatherapy.